Association of Fluid Balance and Survival of Pediatric Patients Treated With Extracorporeal Membrane Oxygenation - Rajapreyar, Prakadeshwari; Castaneda, Lauren; Thompson, Nathan E.; Petersen, Tara L.; Hanson, Sheila J. (Frontiers in Pediatrics, 2021)
The effect of positive fluid balance (FB) on extracorporeal membrane oxygenation (ECMO) outcomes in pediatric patients remains unknown. We sought to evaluate if positive FB in PICU patients with respiratory and/or cardiac failure necessitating ECMO was associated with increased morbidity or mortality. This was a multicenter retrospective cohort study of data from the de-identified PEDiatric ECMO Outcomes Registry (PEDECOR). Patients entered into the database, from 2014 to 2017, who received ECMO support were included. Total of 168 subjects met study criteria. Univariate analysis showed no significant difference in total FB on ECMO days 1-5 between survivors and non-survivors (median 90 mL/kg (IQR 18-208.5) survivors vs. median 139.7 mL/kg (IQR 11.2-300.6) for non-survivors, p = 0.334). There was also no difference in total FB on ECMO days 1-5 in patients with no change in functional outcome as reflected by Pediatric Outcome Performance Category (POPC) score vs. those who had worsening in POPC score >=2 at hospital discharge (median 98 mL/kg (IQR 18-267) vs. median 130 mL/kg (IQR 13-252), p = 0.91). Subjects that required 50ml/kg or more of blood products over the initial five days of ECMO support had an increased rate of mortality with an odds ratio of 5.8 (95% confidence interval of 2.7 – 12.3; p-value = 0.048). Our study showed no association of the noted FB with survival after ECMO cannulation. This FB trend was also not associated with POPC at hospital discharge, MV duration or ECMO duration. The amount of blood product administered was found to be a significant predictor of mortality.